The Silver Web: Sixteenth-Century Maritime Encounters in the Pacific Rim - Cohen, Sharon (The sixteenth century journal, 2020)
The author discusses teaching the history of the movement of silver in the sixteenth century using the history of scale, using the Pacific region as a basis of global, regional, and local scales. Topics include the silver trade; maritime trade history; and relations between Spain and Portugal, the Americas, and Asia.